Reward, punishment, and forgiveness : the thinking and beliefs of ancient Israel in the light of Greek and modern views - Krašovec, Jože. (Supplements to Vetus Testamentum, 1999)
This book deals with central and universal issues of reward, punishment and forgiveness for the first time in a compact and comprehensive way. Until now these themes have received far too little attention in scholarly research both in their own right and in their interrelationship. The scope of this study is to present them in relation to the foundations of our culture. These and related issues are treated primarily within the Hebrew Bible, using the methods of literary analysis. The centrality of these themes in all religions and all cultures has resulted, however, in a comparative investigation, drawing attention to the problem of terminology, the importance of Greek culture for the European tradition, and the fusion of Greek and Jewish-Christian cultures in our modern philosophical and theological systems. This broad perspective shows that the biblical personalist understanding of divine authority and of human righteousness or guilt provides the personalist key to the search for reconciliation in a divided world.